Standardised practices in the networked management of congenital hyperinsulinism: a UK national collaborative consensus - Shaikh, M. Guftar; Lucas-Herald, Angela K.; Dastamani, Antonia; Salomon Estebanez, Maria; Senniappan, Senthil; Abid, Noina; Ahmad, Sumera; Alexander, Sophie; Avatapalle, Bindu; Awan, Neelam; Blair, Hester; Boyle, Roisin; et al. (Frontiers in Endocrinology, 2023)
Congenital hyperinsulinism (CHI) is a condition characterised by severe and recurrent hypoglycaemia in infants and young children caused by inappropriate insulin oversecretion. CHI is of heterogeneous aetiology with a significant genetic component and is often unresponsive to standard medical therapy options. The treatment of CHI can be multifaceted and complex, requiring multidisciplinary input. It is important to manage hypoglycaemia in CHI promptly as the risk of long-term neurodisability arising from neuroglycopaenia is high. The UK CHI consensus on the practice and management of CHI was developed to optimise and harmonise clinical management of patients in centres specialising in CHI as well as in non-specialist centres engaged in collaborative, networked models of care. Using current best practice and a consensus approach, it provides guidance and practical advice in the domains of diagnosis, clinical assessment and treatment to mitigate hypoglycaemia risk and improve long term outcomes for health and well being.